2017
DOI: 10.1016/j.injury.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and hotspots of road traffic injuries in Moshi, Tanzania: An observational study

Abstract: Road traffic injuries (RTIs) continue to increase with the proliferation of motor vehicles, especially in low-income countries where safe road infrastructure is lacking Knowing where and why RTIs occur would allow for increased safety and prevention planning. In this study, police records of 300 motor vehicle collisions which occurred between February 2013 and January 2014 in Moshi, Tanzania, were reviewed. Analysis of variables including victim age, gender, type of collision, conditions, and use of safety equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…Road safety legislation, road infrastructure and affordable ways to maintain vehicles have not kept pace with the surge in vehicle numbers. Studies in Gambia, Burkina Faso and Tanzania have shown that many injuries occur at hot spots such as road intersections with or without traffic lights, during rush hours and at night [2325], and these factors may play a part in Guinea. Human behavior also plays an important role with speeding, careless driving and driving under the influence of alcohol being important factors contributing to RTA in many countries, and probably also in Guinea [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Road safety legislation, road infrastructure and affordable ways to maintain vehicles have not kept pace with the surge in vehicle numbers. Studies in Gambia, Burkina Faso and Tanzania have shown that many injuries occur at hot spots such as road intersections with or without traffic lights, during rush hours and at night [2325], and these factors may play a part in Guinea. Human behavior also plays an important role with speeding, careless driving and driving under the influence of alcohol being important factors contributing to RTA in many countries, and probably also in Guinea [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation to the results we observed in our study is that exposure to risky behavior for injury after alcohol-use might be linked to greater financial status, such as having a car or drinking in proximity with others such as in bars, parties, or restaurants. Some evidence even supports the notion that alcohol-related injuries are cyclical, happening with higher frequency around the weekends or the end of the month when paychecks are delivered (59,60). Similarly, evidence suggests that heavy episodic drinking is more common in households with a higher income (4).…”
Section: Discussionmentioning
confidence: 99%
“…Stands were selected taking into account the spatial distribution that covered the Moshi Urban area, according to their locations. This approach was adopted to include stands that covered all the Moshi Urban geographical area, and also to cover areas for hotspots for motor vehicle crashes defined in a previous publication [ 22 ]. We included two unregistered stands because there were two areas of Moshi Urban that did not have a registered stand.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, RTIs were involved in 43.9% of trauma cases and 66% of traumatic brain injury patients who presented at a hospital in Northwestern Tanzania, making RTIs the most common mechanism of injury [ 20 , 21 ]. Data collected from police records of 300 motor vehicle collisions in Moshi, Tanzania, indicate that the involvement of vulnerable road users, such as motorcyclists, in a traffic crash was directly related to increased injury severity [ 22 ].…”
Section: Introductionmentioning
confidence: 99%